2023
DOI: 10.2196/43224
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Vietnam on the Use of Digital Technologies to Support Patient-Centered Care in Low- and Middle-Income Countries in the Asia-Pacific Region: Scoping Review

Abstract: Background A rapidly aging population, a shifting disease burden and the ongoing threat of infectious disease outbreaks pose major concerns for Vietnam’s health care system. Health disparities are evident in many parts of the country, especially in rural areas, and the population faces inequitable access to patient-centered health care. Vietnam must therefore explore and implement advanced solutions to the provision of patient-centered care, with a view to reducing pressures on the health care syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Unlike previous studies that focused on how to formulate a PCC plan and its effects ( 37 39 ), our study provides a macro perspective on the effect of PCC. We found that PCC can generally improve patients' health status and their subjective necessity of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies that focused on how to formulate a PCC plan and its effects ( 37 39 ), our study provides a macro perspective on the effect of PCC. We found that PCC can generally improve patients' health status and their subjective necessity of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it seems that patients agree to report on their symptoms electronically but they want to talk to a person about their problems as soon as there is something of concern [ 16 , 17 ]. Preferences and participation are also related to the patients’ age, education, and digital literacy [ 9 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%